Response to Hannah Archambault and Luke Pretz, Aaron Benanav, and Ted Burczak. Issue 2 (3rd April 2022) - Adaman, Fikret; Devine, Pat
Abstract : In responding to Fikret Adaman and Pat Devine's essay "Revisiting the Calculation Debate: A Call for a Multiscale Approach, " Hannah Archambault and Luke Pretz, Aaron Benanav, and Ted Burczak at points reinforce the text's positions, reinterpret arguments from different angles, complement arguments, and raise their own concerns. With gratitude, the authors here provide their own reflections on these responses, advocating for politically determined economic priorities, with negotiated-coordination bodies deciding the investments to realize those priorities and with market exchange at the enterprise level. This corresponds to a self-governing society in which the self-realization of individuals can be fully achieved and in which people have real autonomy to participate directly or indirectly in all levels of decision making that affect them.